Detection of circulating free and complexed staphylococcal antigens by enzyme-linked immunosorbent assay. - Lentino, J R (1982)
An enzyme-linked immunosorbent assay was developed for the detection of circulating free and complexed staphylococcal antigens in various clinical categories of staphylococcal infections. Circulating immune complexes were studied by the polyethylene glycol precipitation method. Circulating immune complexes and staphylococcal antigen (at titers of greater than or equal to 1:32) dissociated from the complexes were found in 7 of 8 patients (87.5%) with staphylococcal endocarditis and in 4 of 20 patients with staphylococcal bacteremia (20%). Although the majority of patients did not have detectable free staphylococcal antigen, it was found in three patients with staphylococcal pneumonia. We conclude that detection of complexed antigen in high titer may differentiate patients with staphylococcal endocarditis from those with other forms of staphylococcal infection or transient bacteremia.